The Effectiveness of Group Counseling Program based on a Problem- Solving Method to Reduce Marital Distress among a Sample of Married Women in Jordan - Al. Shoubaki, Naifa (Dirasat: Human and Social Sciences, 2021)
This study aims at exploring the effect of a group-counseling program based on a problem solving method to reduce marital distress among a sample of married women. The sample of the study consisted of (30) married women who obtained the highest scores on a marital distress scale. The sample was divided into two groups: An experimental group which consisted of (15) participants, who received a counseling program in problem solving for a period of (10) weeks, at the rate of one session per week, each session duration (90) minutes. The control group consisted of (15) participants those did not receive the counseling program in problem solving. The researcher developed a measure of the feeling of psychological loneliness and the building of the group counseling program the researcher used the ANCOVA method to investigate the effect of experimental treatment. The results of the study have revealed significant differences in relation to the marital distress variable between the two groups in favor of the experimental group